High-light element thermal damage simulation method based on surface absorptivity
By introducing the concept of equivalent surface absorption, the limitations of the prior art expressing the laser absorption characteristics of the strong light element in the laser are solved, and a more accurate characterization of the comprehensive absorption performance of the lens surface on the laser during laser irradiation is achieved, thereby improving the accuracy of thermal damage simulation.
Patent Information
- Application Number
- CN202510360246.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-25
- Publication Date
- 2025-04-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The prior art has limitations when expressing the absorption characteristics of the strong light element to the laser, which cannot effectively reflect the comprehensive absorption performance of the lens surface to the laser during laser irradiation, and it is impossible to accurately determine whether the lens meets the usage requirements.
The concept of equivalent surface absorption is proposed. By equalizing the surface absorption rates of the lenses, it represents the comprehensive absorption characteristics of the lenses to laser during laser irradiation, and divides the laser irradiation time into multiple time intervals to calculate the equivalent surface absorption rate within each time interval.
It improves the simulation accuracy of thermal damage to bright light elements, reduces simulation errors, and can more accurately represent the absorption characteristics of the lens to the laser during laser radiation, helping to prevent sudden damage to bright light elements caused by pollutants.
Smart Images

Figure CN119885778A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of thermal damage simulation methods, and in particular to a thermal damage simulation method for a strong light element based on surface absorptivity. Background Art
[0002] High-energy laser systems are moving from the laboratory to engineering applications. Studies have found that even when the laser system is running at the designed flux, strong light components are often damaged. As a key component of high-energy laser systems, strong light components have high preparation costs and long processing cycles. After system integration, they are not easy to detect and repair. The damage problem restricts the engineering process of high-energy laser systems.
[0003] Scholars at home and abroad have conducted a lot of theoretical and experimental research on the damage of laser-irradiated optical component materials. The study found that the main mechanism of damage to strong light components is thermal damage caused by abnormal absorption of laser energy by the material, and confirmed that contaminants are the primary factor causing thermal damage to strong light components. The parameters that affect laser absorption mainly include laser wavelength, material chemical composition, material surface state, and surface roughness. Even if the strong light component is fully cleaned before use, contaminants may still adhere to the strong light component during the operation of the high-energy laser system. Therefore, during the use of the laser system, the main factor affecting the absorption of lasers by strong light components is contaminants. Studies have shown that there is a direct relationship between surface absorptivity and thermal damage to optical components. Contaminants will increase the surface absorptivity of strong light components, absorb more energy from the incident laser, and cause thermal damage to strong light components. Exploring the surface absorptivity is helpful to study the thermal damage characteristics of optical components.
[0004] Usually, before laser irradiation, the average surface absorptivity of the lens is measured by photothermal measurement, and the measurement results are used to characterize the absorption characteristics of the lens to the laser during laser irradiation. This method has three problems: First, for uncontaminated lenses with surface defects or uneven surface absorption distribution, the difference between the maximum and minimum absorption rates of the lens surface is too large, and the measured average surface absorptivity is not suitable for representing the absorption characteristics of the entire surface of the lens to the laser, nor can it be used to judge whether the lens meets the use requirements; Second, during laser irradiation, the actual absorption performance of the lens to the laser changes with the increase of laser irradiation time, but the measured surface absorptivity before laser irradiation is a constant value, which cannot represent the absorption characteristics of the lens surface to the laser during laser irradiation; Third, the lens exhibits different absorption characteristics to the laser under different power densities. The measured surface absorptivity before laser irradiation is measured under specific laser conditions and may not reflect the absorption characteristics of the lens to the laser under other laser conditions.
[0005] In summary, studying the effect of laser absorption on the damage of strong light components can strengthen pollution prevention and control in engineering applications, prevent sudden damage of strong light components caused by pollutants, and provide a certain reference for exploring the effect of laser absorption on thermal damage of strong light components under high-energy continuous laser. However, the currently commonly used surface absorption rate measurement value has certain limitations when representing the absorption characteristics of strong light components to lasers. Summary of the invention
[0006] The technical problem to be solved by the present invention is to provide a method for simulating thermal damage of a strong light element based on surface absorptivity in view of the above shortcomings.
[0007] In this simulation method, the concept of equivalent surface absorptivity is proposed to represent the comprehensive absorption characteristics of the lens to the laser during laser irradiation. The equivalent surface absorptivity has two characteristics: first, the lens sample used in the test is considered as a whole, and the surface absorptivity of the lens is equal everywhere. The equivalent surface absorptivity is used to characterize the comprehensive absorption performance of the lens affected by its own surface shape, defects, and use conditions. Secondly, the equivalent surface absorptivity of the lens is a value that changes with the laser irradiation time. Moreover, for the same lens, under different use conditions such as laser power density, its equivalent surface absorptivity is also different, reflecting the influence of laser power density and laser irradiation time on the absorption characteristics.
[0008] The present invention adopts the following technical solutions: A method for simulating thermal damage of a strong light component based on surface absorptivity comprises the following steps: Step 1: Install the lens to be tested on the frame and set the high-energy continuous laser intensity. I 0 ; Step 2: Test the lens t Long-duration laser irradiation and synchronous acquisition t Actual value data of lens surface center temperature change at each moment in time; Step 3: Set the laser irradiation time t Divided into n time interval L, where each L has a value range of: 0.04s ≤ L ≤ t ; Step 4, determining the feasible setting value of the surface absorptivity parameter corresponding to each time interval L, and using COMSOL software to calculate the simulation results of the change of the center temperature of the lens surface in each time interval L when using different feasible setting values of the surface absorptivity parameter; Step 5: Compare the simulation results obtained for the feasible setting value of each surface absorption rate parameter with the actual value data of the lens surface center temperature change obtained in the corresponding time interval L, and calculate the error value corresponding to the feasible setting value of each surface absorption rate parameter in the corresponding time interval L. , select the feasible setting value of the surface absorption rate parameter corresponding to the smallest error value among all feasible setting values in each time interval L as the laser intensity I 0 The equivalent surface absorptivity of the lens in the corresponding time interval L of laser irradiation; Step 6: Use the equivalent surface absorption rate obtained in the previous step to simulate the thermal damage of the high-light component during use.
[0009] Furthermore, the error value The calculation formula is:
[0010] In the formula, T si The first i The experimental data of the sampling points, T fi The first i The simulation data of sampling points, N is the number of sampling points in this time interval L.
[0011] Furthermore, the number of sampling points in each time interval L is the same.
[0012] Furthermore, the duration of each time interval L is the same.
[0013] After adopting the above technical solution, the present invention has the following advantages compared with the prior art: The present invention uses the equivalent surface absorptivity to characterize the absorption characteristics of the strong light element to high-energy continuous laser, establishes a two-dimensional axisymmetric finite element mesh model of the laser-irradiated strong light element, and builds a laser irradiation effect test system. According to the test results, the influence of the surface absorptivity on the thermal damage of the strong light element is analyzed. The equivalent surface absorptivity of the strong light element during laser irradiation is calculated by combining finite element simulation with laser irradiation effect test. The validity and accuracy of the equivalent surface absorptivity are verified by numerical simulation and experimentally measured temperature rise data, and the change law of the equivalent surface absorptivity of the strong light element during laser irradiation is analyzed. The test results verify the correctness of the constructed model. The model parameters are corrected according to the test results, and the equivalent surface absorptivity of the strong light element to the laser is obtained. Compared with the measured surface absorptivity, the simulation error of the equivalent surface absorptivity is smaller and the accuracy is higher.
[0014] The present invention is described in detail below with reference to the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 It is a two-dimensional axisymmetric model of laser irradiated strong light element; Figure 2This is a graph showing the temperature change over time at the center point of the model surface under different mesh divisions; Figure 3 It is the difference diagram between the calculation results of different mesh divisions and ultra-fine mesh divisions; Figure 4 It is the finite element mesh model diagram; Figure 5 This is the laser irradiation effect test system diagram; Figure 6 It is the absorption rate distribution diagram of the measured area on the surface of different lenses; Figure 7 These are the surface images of different lenses under a microscope; Figure 8 It is the surface image of the lens during laser irradiation; Fig. 9 These are the surface images of different lenses after laser irradiation under a microscope; Fig.10 The temperature variation with time curve of experimental measurement and simulated calculation of measured surface absorptivity; Fig.11 This is a graph showing the change of equivalent surface absorption rate of different lenses over time; Fig.12 The temperature variation with time curve of experimental measurement and equivalent surface absorption rate simulation calculation. DETAILED DESCRIPTION
[0016] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.
[0017] First, a finite element model of laser irradiation strong light element is established. The specific process is as follows:
[0018] 1. Model Assumptions A finite element model of laser irradiation strong light element is built based on COMSOL Multiphysics platform. According to the actual use of high-energy laser system, the present invention selects the high-reflection mirror, a typical strong light element in the high-energy laser system, as the research object, and adopts Gaussian distributed continuous laser function in the calculation. Since continuous laser usually causes thermal damage to the material, which manifests as thermal melting damage, the present invention only considers the temperature field when modeling, and ignores the influence of electric field and stress field on material damage. In order to simplify the calculation model, the following assumptions are made: 1) Since the strong light element and heat source studied in the present invention are both axisymmetric, a two-dimensional axisymmetric model is adopted, and it is assumed that the center of the light spot coincides with the center of the surface of the strong light element.
[0019] 2) This invention mainly studies the temperature change before the material is thermally damaged under laser irradiation, and does not consider the temperature rise process after the material reaches the melting point and undergoes phase change. Therefore, it is assumed that the materials interacting with the laser are all isotropic and uniform materials, and the slight changes in thermal parameters are ignored during the temperature change process, and the thermal parameters are considered to be constant.
[0020] 3) Ignoring the loss in the energy conversion process, it is assumed that all the laser energy absorbed by the material is converted into heat energy.
[0021] 4) When high-energy continuous laser acts on a strong light element, the energy lost by thermal radiation on the surface of the strong light element is not considered, and the thermal convection process between the surface of the strong light element and the air is stable.
[0022] 5) Since the size of the pollutant is much smaller than that of the strong light element, it mainly affects the surface absorptivity of the strong light element. Therefore, the model ignores the geometric parameters and thermophysical parameters of the pollutant and only considers the effect of the pollutant on the surface absorptivity.
[0023] 2. Model building A two-dimensional axisymmetric model of a laser-irradiated strong light component is constructed. Assume that the laser beam is Gaussian distributed and vertically incident on the surface of the coated strong light component. Figure 1 shown.
[0024] In the figure, the origin of the coordinate system in the cylindrical coordinate system is Point is the center of the laser incident surface of the sample, is the longitudinal direction of the material, is the radial direction of the material, and the laser irradiation direction is Axis direction, is the spot radius of the incident laser, is the radius of the bright light element, is the thickness of the strong light element, is the thickness of the high reflectivity film, is the thickness of the low reflectivity film, is the base thickness.
[0025] The material irradiated by the laser generates a temperature rise due to the absorption of laser energy, and at the same time, the energy is conducted and diffused around the laser irradiated area in the form of heat conduction. Based on the classical Fourier heat conduction law and the law of conservation of energy for solid heat conduction, the heat conduction equation of the strong light element in the cylindrical coordinate system can be determined as: (1) In formula (1), express Always The temperature of the location, is the laser irradiation time, is the density of the material, is the specific heat capacity of the material, is the thermal conductivity of the material, is the heat source generated by the laser acting on the material. When the laser satisfies the Gaussian distribution, the heat source in the formula It can be expressed as: (2) In formula (2), , are the radial and axial positions in the axisymmetric coordinate system, is the absorption coefficient of the material to the incident laser, is the reflectivity of the material to the incident laser, is the laser spot radius, is the incident laser center power density (hereinafter referred to as laser power density).
[0026] For high-reflection film coated strong light components, the material has a shallow absorption depth for the incident laser, and the effect of the laser can be regarded as a heat source, so the surface absorption rate is used. A represents the absorption rate of the incident laser on the material surface, replacing , then formula (2) can be expressed as: (3) From formula (3), we can see that the laser intensity The surface absorption rate of the material A Directly affects the size of the heat source on the material surface.
[0027] At the initial moment of laser irradiation, the temperature distribution of the strong light element is balanced, and the initial temperature T 0 is the same as the ambient temperature. During the laser irradiation process, the initial conditions and boundary conditions of the model are as follows: is the surface heat transfer coefficient, T 0 represents the ambient temperature (in K).
[0028] (4) (5) (6) Based on the above models and formulas, the temperature distribution of the strong light element under laser irradiation at any time can be obtained by simulation calculation using the finite element analysis software COMSOL.
[0029] 3. Model parameter setting According to the research object selected by the present invention, the geometric dimensions of the model and the thermal physical property parameters of the materials are set.
[0030] The radius of the strong light element a=25mm high-reflection film-coated plane mirror, high-reflectivity film thickness h 1=1658nm, low reflectivity film thickness h 2 = 2183nm, substrate thickness h 3=3mm. The high reflectivity film material is ZrO2, the low reflectivity film material is SiO2, and the base material is fused quartz. Table 1 gives the thermal physical parameters of the high light component materials.
[0031] Table 1 Thermophysical parameters of high-intensity light component materials
[0032] During the laser irradiation of the strong light element, the air convection process is stable, and the surface heat exchange coefficient is taken , laser power density I 0. Initial temperature T 0 and surface absorption A The setting needs to refer to the measured values in the laser irradiation test.
[0033] 4. Finite element meshing The finite element algorithm discretizes the complex structure into a finite model represented by a unit assembly for calculation. The grid division of appropriate size is conducive to the efficient solution of the model. In the calculation of the present invention, the Gaussian laser irradiates the central area of the surface of the geometric model. The temperature of the model generally shows that the upper surface temperature is the highest and the temperature decreases along the axial direction. Therefore, the grid division of the model is also mainly based on the principle that the upper surface is the densest and becomes sparse along the axial direction. The selection of triangular grid has a better division effect.
[0034] The surface spot area of the model is the key part of the temperature analysis, and the mesh unit size parameters should be customized for the model surface. Since the minimum film thickness is 0.00166mm, the model surface unit size is set to 0.001mm.
[0035] Select predefined meshing for other areas of the model. Use super coarse, coarse, normal, fine, and super fine meshing to mesh the model respectively. Keep other calculation parameters of the model consistent, and calculate the surface center temperature of the model with different meshing under the same time step. Figure 2 It represents the change of temperature with time under different grid divisions during the temperature rise process. Figure 3 It represents the difference between the calculation results of different mesh divisions and ultra-fine mesh divisions during the temperature rise process.
[0036] from Figure 2 It can be seen that the change of the temperature at the center point of the model surface over time is not affected by the number of grids. Figure 3It can be seen that as the number of grids increases, the calculation results are getting closer and closer to the calculation results of the densest grid division. The difference between the calculation results using conventional grid division and ultra-fine grid division is less than 0.7K throughout the process. Continuing to increase the number of grids, the calculation results of the refined grid division are not much different from the calculation results of the conventional grid division. Therefore, under the premise of taking into account both calculation accuracy and calculation efficiency, the present invention selects conventional grid division. The minimum unit size of the grid is 0.0075, and the maximum unit size is 1.68mm. Establish a grid model such as Figure 4 As shown, the complete mesh contains 164585 domain cells and 30570 boundary cells.
[0037] Then the laser irradiation strong light element test is carried out, and the specific process is as follows:
[0038] 1. Handling of test samples The test sample is a customized high-reflection mirror, and the material parameters are consistent with the simulation calculation parameters.
[0039] During the use of high-energy laser systems, metal structural parts inside the system may produce particle contaminants due to wear, oxidation, and ablation of stray light. The size of these particle contaminants ranges from 1 to 30 μm, and the main materials of the contaminants include titanium alloy and aluminum oxide. The surface absorption rate of the lens is mainly affected by the contaminants, so the surface absorption rate of the lens can be changed through pollution treatment, and the test samples are divided into two states: contaminated and uncontaminated.
[0040] Before the experiment, use ultra-fine industrial dust-free wipes dipped in ethanol to wipe lenses (I) and (II) to ensure that lenses (I) and (II) are in a pollution-free state. Titanium alloy, a common pollutant material in high-energy laser systems, was selected to treat the pollution of lenses (III) and (IV). The pollution treatment method is: in a 10,000-class clean room, add 10ml of ethanol and 1g of micron-grade titanium alloy particles to a crystallization beaker, stir the ethanol solution for 10s, and suspend the pollutant particles in ethanol. Use a clean pipette to absorb 2ml of the pollutant solution, place the test tube against the surface of the high-reflection mirror sample, and slowly drip the pollutant solution onto the surface of the lens. The pollutant solution spreads evenly on the surface of the lens, and the pollutant particles will adhere to the surface of the sample after the ethanol evaporates.
[0041] 2. Construction of the test system This section builds a laser irradiation effect test system. The system structure diagram and physical diagram are shown in the figure below. Figure 5 shown.
[0042] The high-power continuous fiber laser model RFL-C8000 used in the test has a Gaussian beam output wavelength of 1064nm and an output power of up to 8000W. Before the test began, the laser was tested for stability and operated continuously for half an hour. The RMS value of the power fluctuation was observed to be less than 2%, and its power stability met the use requirements.
[0043] The laser emitted by the laser passes through a converging system composed of several lenses with different focal lengths and is vertically incident on the center of the high-reflectivity mirror sample to be tested. Before the test, the spot position is adjusted so that the center of the spot coincides with the center of the lens surface and the spot radius r 0 refers to the radius of the spot formed on the focal plane after the beam passes through the lens, which is obtained by measuring the 86.5% ring radius with a beam quality analyzer (Primes FocusMonitor+). Set the spot radius according to the test conditions and the typical value of the high-energy laser system. r 0=1mm.
[0044] Due to the limitation of the laboratory refrigeration system load, during the test, the lens was first irradiated with a lower power density detection light for 10 seconds. After observing that the lens was not damaged, a higher power density test light was used to test to avoid serious damage to the sample and test instrument due to excessive laser power density. The laser parameters used in the test are shown in Table 2.
[0045] Table 2 Laser parameters
[0046] In the test, a non-contact infrared thermometer (model DH-IPC-HFW5433K-33T) was used to measure the temperature change on the surface of the lens under test. The collected temperature data was discrete data with a time step of 0.04s. During the test, the temperature data measured by the thermometer would fluctuate slightly because it was affected by the surrounding area and the ambient temperature of the test point when collecting the temperature.
[0047] During the test, a visible light camera was used to record the surface morphology of the lens. The model of the visible light camera is AO-HK830-5870, with 8.3 million pixels and a resolution of 3840×2160.
[0048] The entire test was completed in a Class 100 clean room, and the laboratory environment temperature was maintained at 293K (±1K). During the test, the laser reflected from the tested lens was collected by the optical trash can after passing through the reflector and filter. At the same time, a diffuse reflection screen was placed around the test system to receive stray light to prevent the laser from injuring the test personnel or damaging other devices. During the laser emission process, the test personnel should operate behind the diffuse reflection screen to ensure the safety of the test process.
[0049] 3. Measurement of surface absorption The two-dimensional photothermal scanning microscope model PTM-2000 used in the present invention has a detection wavelength of 1064nm and a detection sensitivity of 0.1ppm. The surface absorptivity of the test sample is measured non-contactly by photothermal measurement, which is used for setting simulation parameters and analyzing the surface absorption characteristics of the sample.
[0050] In order to determine the surface absorption rate of the lens in the spot area in the test, the 2mm×2mm area in the center of the surface of four lenses (Ⅰ), (Ⅱ), (Ⅲ), and (Ⅳ) was selected for measurement. The number of test points was ≥10000 and the test environment temperature was 293K. The measurement results are shown in the figure below. Figure 6 As shown in Table 3, the red area in the figure indicates the strong absorption point on the lens surface. The unit of absorption rate is ppm, which means one part per million.
[0051] Table 3 Surface absorptivity distribution of different lenses
[0052] The average surface absorptivity is usually used to express the absorption characteristics of the lens surface to the laser. From the measurement results, it can be seen that the surface absorptivity of the lens is unevenly distributed. The surface absorptivity of the uncontaminated lenses (I) and (II) is low, and the surface absorptivity of the contaminated lens (IV) is 4 orders of magnitude higher than that of the uncontaminated lens. However, the surface absorptivity of the contaminated lens (III) is low, and the measurement result is similar to that of the uncontaminated lens. Therefore, before actual use, it is impossible to screen out all contaminated lenses by measuring the surface absorptivity.
[0053] 4. Observation of surface microstructure The central area of the surface of the test sample was observed using a three-dimensional digital microscope (Keyence VHX-5000). Figure 7 shown.
[0054] Since the test samples are transparent plane mirrors, the uncontaminated lenses (I) and (II) only show the base color of the table in the field of view after magnification. After magnification of the contaminated lenses (III) and (IV), it can be seen that there are randomly distributed spherical titanium alloy contaminant particles on the surface. The size of the contaminant particles is between 1 and 30 μm, and the contaminants may be connected or stacked on the lens surface. Compared with lens (IV), the surface contaminants of lens (III) are smaller in size and sparsely distributed. Figure 6 The absorption rate distribution in is consistent with that in .
[0055] The test results are analyzed as follows: 1. Observation of the surface image of the strong light element Under the action of Gaussian distributed laser, the temperature at the center of the material surface is the highest and the temperature rise rate is the fastest, and the decomposition temperature of the material is reached first. Therefore, the present invention selects the center temperature of the lens surface for analysis, and uses the melting point of the film material ZrO2, 2680K, as the criterion for lens damage.
[0056] use I 0=2kW cm -2 When the detection light irradiates the lenses, there is no obvious temperature rise in the center of the surface of lenses (Ⅰ), (Ⅱ) and (Ⅲ), and the temperature rise in the center of the surface of lens (Ⅳ) exceeds 80K. None of the four lenses are damaged.
[0057] use I 0=255kW·cm -2 During the process of the test light irradiating the lens, lenses (I), (II) and (III) were not damaged, but lens (IV) was damaged at the moment of laser emission. The visible light camera monitored the surface image of the lens during the laser irradiation process. Figure 8 shown.
[0058] After the laser irradiation, the lens (III) was wiped with ethanol using an ultra-fine industrial dust-free wipe, and the central area of the surface of the test sample was observed using a three-dimensional digital microscope. Fig. 9 shown.
[0059] observe Figure 8 and Fig. 9 It can be seen that under the same laser power density, the contaminated lens with lower surface absorption rate absorbs less energy. Stopping the light and cleaning before the lens is thermally damaged can remove the influence of the contaminants on the lens and improve the utilization rate of the lens. The contaminated lens with higher surface absorption rate will absorb more energy and cause abnormal temperature rise on the lens surface. When the temperature reaches the melting point of the contaminant material, the contaminant will burn and splash outward, and the heat will radiate visible light that can be detected by the naked eye; when the temperature reaches the melting point of the lens film material, it will cause the film material to melt, causing irreversible damage to the lens.
[0060] 2. Comparison between simulation and experiment of temperature rise process of strong light element The damage of lens (Ⅳ) occurred within the temperature acquisition step of 0.04s of the infrared thermometer, and no data of the temperature rise process was collected. Therefore, the average surface absorption rate of the lens measured in Table 3 was used. A avg The temperature rise process of lenses (Ⅰ), (Ⅱ), and (Ⅲ) is calculated as simulation parameter values and compared with the experimental measurement data. Fig.10 shown.
[0061] from Fig.10It can be seen that under the irradiation of high-energy continuous laser, the rate of increase of the center temperature of the lens surface decreases with the increase of time. Under the same laser irradiation conditions, the higher the surface absorption rate, the greater the temperature rise of the center of the lens surface.
[0062] from Fig.10 As shown in Figure (a), during the laser irradiation process, the simulation results in the early stage are larger than the experimental data, while the simulation results in the later stage are smaller. Fig.10 In Figure (b), the simulation data is significantly lower than the test data. This is because the use of the measured average surface absorptivity in simulation calculations to express the absorption characteristics of the lens surface to the laser has limitations. In fact, the surface absorptivity of the lens is unevenly distributed and may change with the increase of laser irradiation time.
[0063] 3. Calculation of equivalent surface absorption rate In order to further explore the absorption performance of the lens surface to laser during laser irradiation, the equivalent surface absorption rate is proposed in the research of this invention in view of the limitations of the measured equivalent surface absorption rate. A t The concept refers to the comprehensive absorption characteristics of the laser on the surface of the lens irradiated by the laser during the laser irradiation process. The equivalent surface absorptivity has two characteristics: first, the lens sample used in the test is considered as a whole, and the surface absorptivity of the lens is equal everywhere. The equivalent surface absorptivity is used to characterize the comprehensive absorption performance of the lens affected by its own defects, pollutants, and use conditions. Secondly, the equivalent surface absorptivity of the lens is a value that changes with the laser irradiation time, and for the same lens, under different use conditions such as spot position and laser power density, its equivalent surface absorptivity is also different.
[0064] First, the simulation error To define: (7) in, T s is the experimental data, T f is the simulation data, N is the number of sampling points.
[0065] The calculation method of equivalent surface absorption rate is: tDivide into several time intervals L, assume that the equivalent surface absorptivity of the lens in each time interval L is constant, use the surface absorptivity parametric scan in COMSOL, calculate the temperature rise of the center of the lens surface in each time interval L, and calculate the error between the simulation results and the test results corresponding to different surface absorptivity parameters. The surface absorptivity simulation parameter value corresponding to the simulation result with the smallest error is the equivalent surface absorptivity in the time interval corresponding to this temperature rise data. The equivalent surface absorptivity unit is ppm, and the value is accurate to one decimal place.
[0066] In order to eliminate the influence of temperature measurement data fluctuation and limited range, when selecting the value of L, it should be ensured that the temperature measured in the L time period is within the range and has a clear upward trend. Therefore, in the calculation of the present invention, L is at least greater than 1s.
[0067] Select L=1s, L=2s, and L=3s for calculation, and obtain the change of equivalent surface absorptivity of the lens with laser irradiation time during laser irradiation. Fig.11 shown.
[0068] contrast Fig.11 In the figure, the change of equivalent surface absorptivity of the lens with time under different L values. It can be seen that the value of L has an impact on the calculation result of the equivalent surface absorptivity, but does not change the trend of the equivalent surface absorptivity changing with the laser irradiation time. Without considering the influence of temperature measurement data fluctuations, the smaller the value of L, the more obvious the law of the change of equivalent surface absorptivity with laser irradiation time. Therefore, the present invention mainly analyzes the calculation result of the equivalent surface absorptivity when L=1s.
[0069] The equivalent surface absorption rate calculated using L=1s is used for simulation. The calculated results and the temperature variation curve measured in the experiment are shown in the figure below. Fig.12 shown.
[0070] according to Fig.11 and Fig.12 It can be seen that the measured surface absorptivity and equivalent surface absorptivity of the uncontaminated lens are relatively close, but the measured surface absorptivity and equivalent surface absorptivity of the contaminated lens are quite different. The measured surface absorptivity of the contaminated lens (III) is similar to that of the uncontaminated lens (I), but the equivalent surface absorptivity differs by 10 times. During the laser irradiation process, under the premise that no new contaminants are introduced, the rate of increase of the equivalent surface absorptivity of the lens decreases with the increase of laser irradiation time.
[0071] According to the study of the absorption behavior of optical coatings in high average power laser applications by researchers at the Livermore Laboratory in the United States in 2000, it was found through experiments that "there is a relationship between the absorptivity and the laser irradiation time: as the laser irradiation time increases, the absorptivity increases at a decreasing rate." The analysis results of this section on the change of the equivalent surface absorptivity of the tested lens over time are consistent with the above research results, verifying the effectiveness of the calculation method of the equivalent surface absorptivity proposed in the present invention.
[0072] The proposal of equivalent surface absorptivity has two meanings: first, the temperature data obtained from the experiment is discrete data. The simulation based on equivalent surface absorptivity can calculate the temperature data within the acquisition step of the infrared thermometer, and the simulation results can be used to further analyze the transient changes in the surface temperature of the lens under laser irradiation. Second, in the actual use of the lens, the appearance of contaminants cannot be predicted, and the surface absorptivity of the lens may suddenly change due to the appearance of contaminants. Therefore, during the laser irradiation process, the equivalent surface absorptivity should be calculated based on the actual monitored temperature rise data, and the equivalent surface absorptivity should be used to express the absorption characteristics of the lens to the laser during the laser irradiation process.
[0073] The temperature rise process is calculated using the measured surface absorptivity and the equivalent surface absorptivity. The errors between the simulation data and the experimental data are shown in Table 4: Table 4 Errors between simulation data and test data for different lenses
[0074] According to Table 4, there may be a large error between the simulation results using the surface absorptivity measured before the test and the test results. The simulation data calculated using the equivalent surface absorptivity is in good agreement with the test data, with an error of less than 0.05%, which verifies the effectiveness and high precision of the simulation calculation and the equivalent surface absorptivity. The equivalent surface absorptivity can better represent the absorption characteristics of the lens surface to the laser during laser irradiation.
[0075] The present invention simulates and tests the thermal damage of the high-reflection mirror of a typical strong light component under high-energy continuous laser; and proposes to use the equivalent surface absorptivity to characterize the comprehensive absorption performance of the strong light component to the laser; and uses the actual temperature rise data of the lens during laser irradiation to adjust the surface absorptivity parameter value in the simulation calculation, so as to obtain the equivalent surface absorptivity of the lens that changes with the laser irradiation time. The results show that: 1) Defects and contaminants can cause uneven distribution of surface absorptivity of high-intensity light components. For such high-intensity light components, the measured average surface absorptivity has limitations in characterizing the component's absorption characteristics of lasers.
[0076] 2) Pollutants mainly increase the temperature accumulation rate on the lens surface by increasing the surface absorption rate of the lens, thereby causing thermal damage to the lens; titanium alloy pollutants can increase the surface absorption rate of the lens by 1 to 4 orders of magnitude; stopping the light in time and cleaning or refurbishing the lens before thermal damage occurs on the lens surface can avoid thermal damage to the lens caused by pollutants, improve the utilization rate of the lens, and extend the service life of the lens.
[0077] 3) Compared with the surface absorptivity measured before the lens is used, the simulation error of the equivalent surface absorptivity is smaller and the accuracy is higher, which can better represent the comprehensive absorption performance of the lens to laser during laser irradiation.
[0078] 4) The equivalent surface absorptivity of the lens increases with the increase of laser irradiation time, and the rate of increase decreases with time. By monitoring the change of equivalent surface absorptivity during laser irradiation, the light can be stopped in time when the equivalent surface absorptivity changes suddenly or increases to a certain value, avoiding irreparable serious damage to the lens.
[0079] The above is an example of the best implementation of the present invention, and the parts not described in detail are common knowledge of ordinary technicians in the field. The protection scope of the present invention shall be based on the content of the claims, and any equivalent transformation based on the technical enlightenment of the present invention is also within the protection scope of the present invention.
Claims
1. A method for simulating thermal damage of a strong light component based on surface absorptivity, characterized in that: The following steps are involved: Step 1: Install the lens to be tested on the frame and set the high-energy continuous laser intensity. I 0 ; Step 2: Test the lens t Long-duration laser irradiation and synchronous acquisition t Actual value data of lens surface center temperature change at each moment in time; Step 3: Set the laser irradiation time t Divided into n time intervals L, where each L has a value range of: 0.04s ≤ L ≤ t ; Step 4, determining the feasible setting value of the surface absorptivity parameter corresponding to each time interval L, and using COMSOL software to calculate the simulation results of the change of the center temperature of the lens surface in each time interval L when using different feasible setting values of the surface absorptivity parameter; Step 5: Compare the simulation results obtained for the feasible setting value of each surface absorption rate parameter with the actual value data of the lens surface center temperature change obtained in the corresponding time interval L, and calculate the error value corresponding to the feasible setting value of each surface absorption rate parameter in the corresponding time interval L. , select the feasible setting value of the surface absorption rate parameter corresponding to the smallest error value among all feasible setting values in each time interval L as the laser intensity I 0 The equivalent surface absorptivity of the lens in the corresponding time interval L of laser irradiation; Step 6: Use the equivalent surface absorption rate obtained in the previous step to simulate the thermal damage of the high-light component during use.
2. The method for simulating thermal damage of a strong light element based on surface absorptivity according to claim 1, characterized in that: Error value The calculation formula is: ; In the formula, T si The first i The experimental data of the sampling points, T fi The first i The simulation data of sampling points, N is the number of sampling points in this time interval L.
3. The method for simulating thermal damage of a strong light element based on surface absorptivity according to claim 2, characterized in that: The number of sampling points in each time interval L is the same.
4. The method for simulating thermal damage of a strong light element based on surface absorptivity according to claim 2, characterized in that: The duration of each time interval L is the same.
Citation Information
Patent Citations
Simulation extrapolation method for transmission power and specific absorption rate of resonant radiation device
CN113051793A
Method and system for predicting damage time of laser irradiation metal material
CN117852361A
Multi-field coupling solution method for intense laser-driven explosion shock
CN118709590A
Method for evaluating quality of metal parts
CN119618113A
System and method for adaptive beamforming for specific absorption rate control
US20110059706A1